2018
DOI: 10.1029/2018jc013788
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Surface Wave Dispersion in the Marginal Ice Zone

Abstract: This study presents the most comprehensive set of in situ and remote sensing measurements of wave number, and hence the dispersion relation, in ice to date. A number of surface‐following buoys were deployed in sea ice from the R/V Sikuliaq, which also hosted an X‐band marine radar, during the ONR Arctic Sea State field experiment. The heave‐slope‐correlation method was used to estimate the root‐mean‐square wave number from the buoys. The method was highly sensitive to noise, and extensive quality control measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…As the open water dispersion relation is likely to hold for waves in the MIZ with periods in the range of 3-10 s (Collins et al, 2018), a linear paradigm is used to model the wave propagation speed. As the open water dispersion relation is likely to hold for waves in the MIZ with periods in the range of 3-10 s (Collins et al, 2018), a linear paradigm is used to model the wave propagation speed.…”
Section: 1029/2019gl082945mentioning
confidence: 99%
“…As the open water dispersion relation is likely to hold for waves in the MIZ with periods in the range of 3-10 s (Collins et al, 2018), a linear paradigm is used to model the wave propagation speed. As the open water dispersion relation is likely to hold for waves in the MIZ with periods in the range of 3-10 s (Collins et al, 2018), a linear paradigm is used to model the wave propagation speed.…”
Section: 1029/2019gl082945mentioning
confidence: 99%
“…However, the former uses the Doble buoys, while the latter uses SWIFT buoys operated by the University of Washington (Thomson, ), which are equipped with cameras, required for the ice‐type observation reported here (W. E. Rogers, private communication, 2019). In Figure c, we show the normalized wavenumber data of Collins et al () using h =4,18,30 cm, with the first two values being the lower and upper bounds of h that we assume for the Arctic attenuation rate data in Figure b. Despite the uncertainty in h , the field wavenumber data set collapses onto the laboratory data sets in the normalized plane; see Figure c.…”
Section: Application To Datamentioning
confidence: 92%
“…Collins et al () analyzed the data and concluded that the effect of ice on wavelength is insignificant for frequencies f <0.3 Hz. Since Collins et al's () data set (see Figure 14 in that paper) presents measurements of wavenumber rather than attenuation rate, we include it in Figures a and c, comparing with the laboratory data sets of wavenumber. Collins et al () reported that the ice layer thickness h <30 cm with loose pancakes and frazil ice.…”
Section: Application To Datamentioning
confidence: 99%
See 2 more Smart Citations